The Influence of the Use of Interactive Learning Media on the Learning Outcomes of Midwifery Students - Al-bahra Al-Bahra; Hardjito S. Darmojo; Siti Madinah Ladjamuddin (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2024)
Background: Technological developments in health education are driving a transformation of learning toward interactive digital media. In midwifery education, interactive learning media such as videos, digital simulations, and e-learning are expected to improve student learning outcomes, encompassing cognitive, affective, and psychomotor aspects. However, the effectiveness of their implementation still requires in-depth study within the context of student experiences. Objective: This study aims to explore the influence of the use of interactive learning media on midwifery student learning outcomes based on their learning experiences. Methods: This study used a qualitative approach with a phenomenological design. Participants consisted of 12 midwifery students selected using purposive sampling based on the criteria of having participated in interactive media-based learning. Data were collected through in-depth interviews, observation, and documentation. Data were then analyzed using the Miles, Huberman, and Saldaña model, encompassing the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation of sources, methods, and member checking. Results: The study revealed four main themes: improved understanding of learning materials, increased motivation and engagement in learning, increased readiness for clinical practice, and challenges in implementing technology. Interactive learning media helped students understand complex midwifery concepts through visualization and simulation, increased learning motivation through more engaging learning, and improved readiness for clinical practice. However, limited internet access and technological infrastructure remain barriers to optimal implementation. Conclusion: Interactive learning media positively impacted midwifery students' learning outcomes across cognitive, affective, and psychomotor domains. Integrating interactive learning media into the midwifery education curriculum is highly recommended to improve the quality of competent and adaptable graduates in the digital era.